Numerical and model tests of soil retaining structure using piles and geosynthetic reinforcement elements - Lukpanov, Рауан; Zhaksybekova, Жанагуль (Рroblems of engineering and professional education, 2023)
The article presents the stages of the numerical and model tests of a soil embankment with retaining structures. The tests were carried out to determine the effectiveness of geosynthetics for the optimal design solution of retaining structures.